A transitivity analysis of the short story The little match girl" by Hans Christian Andersen = Phân tích chuyển tác trong truyện ngắn “Cô bé bán diêm” của Hans Christian Andersen . M.A Thesis Linguistics: 60 22 15" - Nguyễn, Thị Thanh Tâm (University of Languages and International Studies, 2017)
41 p. + CD-ROM